Utility of contrast-enhanced magnetic resonance lymphangiography for yellow nail syndrome with lymphangiopathy: a case report. Issue 7 (26th July 2022) - Shimanuki, Yui; Miyoshi, Shion; Anzai, Nanami; Usui, Yusuke; Shiraga, Nobuyuki; Kishi, Kazuma
ABSTRACT: Yellow nail syndrome (YNS) is a rare disorder characterized by the triad of yellow nails, lymphedema and chronic respiratory manifestations. Lymphatic abnormalities are a characteristic finding of YNS. Nevertheless, proof of lymphatic vessel abnormality by direct needle puncture for contrast agent injection is technically challenging because the lymphatic vessels in YNS are dysplastic. Thus, we opted for contrast-enhanced magnetic resonance (MR) lymphangiography with subcutaneous injection in patients suspected of YNS to facilitate easier comprehensive lymphatic vessel visualization. The lymphatic vessels of the thighs were few and barely recognizable, indicating weak flow cranially and lymphatic vessel hypoplasia. These findings were suggestive of dysplasia of the lymphatic vessels. Therefore, MR lymphangiography may be a useful novel diagnostic modality for YNS.